Economic impacts of lameness in feedlot cattle. Issue 4 (1st December 2017) - Davis-Unger, J.; Pajor, E. A.; Schwartzkopf-Genswein, K.; Marti, S.; Dorin, C.; Spackman, E.; Orsel, K.
Abstract: Lameness is an important health issue in feedlot cattle; however, there is a paucity of information regarding its economic impact. Decision tree models are excellent tools for assessing costs of disease such as the net return (net return = benefit – cost). Models were developed using expert opinion, literature and retrospective feedlot data provided by Vet-Agri Health Services (VAHS, Airdrie, Alberta, Canada) collected from 2005 to 2015 on individually treated cattle ( n = 30, 940) from 28 feedlots. The objective was to estimate net return of various lameness diagnoses and impacts of cattle type, season of treatment, and extreme high and low cattle prices. Cattle were diagnosed as lame according to the following categories: foot rot, foot rot in heavy cattle (BW > 363 kg at treatment), injury, lame with no visible swelling, and joint infection. Records consisted of arrival and treatment weight, cost of treatment, and cattle deaths. Records included cattle types classified as: fall calves (heifer and steer), winter calves (heifer and steer) and yearling cattle (heifer and steer). Lastly, variables ADG, days on feed (DOF), and Season (spring, summer, fall, and winter) were created. Models estimated net return using cattle slaughter prices for healthy cattle that reached a slaughter weight of 635 kg and for three possible outcomes for each diagnosis after final treatment: cattle that recovered after treatment and reached a slaughter weight of 635 kg; cattle that were removed before they reached slaughter weight; or cattle that died. Compared to undiagnosed cattle with 1.36 kg/d ADG, cattle diagnosed with foot rot and foot rot heavy cattle had the highest ADG until first treatment (1.14 and 1.57 kg/d, respectively) and differed significantly ( P < 0.05) compared to cattle diagnosed with injuries (0.87 kg/d), lame with no visible swelling (0.64 kg/d), and joint infections (0.53 kg/d). Yearling steers had the most positive returns compared to all other cattle types. Cattle with lighter arrival weight had lower ADG and increased economic losses after treatment compared to heavier weighted cattle on arrival. Based on average slaughter prices over a 10-yr period for healthy cattle, return was 690. Return after final treatment for cattle with foot rot was 568, foot rot in heavy cattle was 695, and injury was 259. However, joint infections and lame with no visible swelling had negative returns of –286 and –701, respectively.